Highly efficient flame retardant and smoke suppression mechanism of boron modified graphene Oxide/Poly(Lactic acid) nanocomposites. (September 2019) - Tawiah, Benjamin; Yu, Bin; Yuen, Richard K.K.; Hu, Yuan; Wei, Ruichao; Xin, John H.; Fei, Bin
Abstract: Simultaneous flame retardancy and tensile strength enhancement of poly(lactic acid) (PLA) is particularly important due to its eco-friendliness and potential application as an engineering plastic. This work investigates the application of azo-boron (AZOB) modified reduced graphene oxide (RGO) intercalated by sodium metaborate (SMB) for simultaneous flame retardant (FR), smoke/toxic fumes suppression and tensile strength enhancement of PLA nanocomposites. The RGO-AZOB/SMB hybrid was prepared by aryl grafting of AZOB on GO followed by in-situ reduction/intercalation with sodium borohydride/SMB. Then RGO-AZOB/SMB hybrid was incorporated into PLA, and the properties were examined. Cone calorimeter test demonstrates improved FR performance by substantial reductions in peak heat release rate ∼76.5%, total heat release ∼76.9%, total smoke release ∼55.6%, peak CO production ∼25.9% and peak CO2 production by ∼78.6%. A V-0 rating was attained in the UL 94 test with a higher LOI value of 31.2%. Considerable reductions in pyrolysis products, mainly hydrocarbons, CO, CO2, and carbonyl compounds were observed. The tensile strength and Young's Modulus were improved by 49.1% and 34.9% respectively. The FR mechanism of RGO-AZOB/SMB/PLA nanocomposites is based primarily on the glassy charring effect of the B–OH groups in AZOB and the inherent lamellar blocking effect of RGO. Graphical abstract: Image 1